Parallel Multi-Stage & Multi-Step Method in ODEs (Journal of Computational Mathematics, 2000)
In this paper, the theory of parallel multi-stage and multi-step method is discussed, which is a form of combining Runge-Kutta method with linear multi-step method that can be used for parallel computation. \u00a0
Keywords: Ordinary differential equations; Parallel simulation.